IQ Difference before and after Temporal Lobe Epilepsy Surgery: First report from Indonesia - Muhamad Thohar Arifin1 , Fajar H. Niantiarno1 , Nabila Amalina1 , Hardian2 , Muttaqin Z (Institute of Medico-legal Publications Pvt Ltd, 2020)
Epilepsy is a serious disorder of the brain, affects almost fifty million people in the world. About 40% of the patients finally became refractory to epileptic drugs, especially those with temporal lobe epilepsy (TLE). This refractory condition may cause psychosocial decline, including patient’s intelligence. Surgical therapy has an important role in stopping further damage to brain cells caused by repeated seizures. The elimination of the seizure after surgery will hopefully results in better intelligence score. This study aims to find out the effect ofsurgical therapyin TLE patients after surgery. We were using a Quasi Experimental study with One Group Pre-test and Post-test design. The samples were taken with consecutive sampling method. Subjects were 15 TLE patients who underwent anterior temporal lobectomy and have passed at least one year postoperative period, and also had done an intelligence quotient (IQ) test before surgery. IQ before and after surgery were measured with WAIS and WISC-R method. The statistical tests used were paired t-test. We found the verbal IQ after surgery(98.8±9.88(76-119)) were significantly higher(p=0.01) comparedwithpreoperativeverbalIQ(92.7±9.60(77-113)). On the other hand, performance IQ after surgery (98.2±8.64(82-115)) were higher compared with preoperative performance IQ (96.0±9.39(75-116)) but it was not significant (p=0.5). Total IQ after surgery (97.8 ±7.69(81-107)) also higher compared with preoperative total IQ (93.9±9.28(75-115)) but also not significant (p=0.08). Postoperative verbal IQ improvement was found compared with preoperative verbal IQ.